Determination of stress index: approach and challenges - Syahrull Hi-Fi Syam, Ahmad Jamil; Sazali, Yaacob; Paulraj, M.P; Ku Halim, Ku Ariffin (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.